Perceived Parental Rejection Mediates the Influence of Serotonin Transporter Gene (5-HTTLPR) Polymorphisms on Impulsivity in Japanese Adults - Nishikawa, Saori (Public Library of Science, 2012)
This study examined (1) the interrelationships among 5-HTTLPR genotype, perceived parental rejection, and impulsivity, and (2) meditational models in which perceived paternal/maternal rejection mediates the relationship between the 5-HTTLPR genotype and impulsive behaviour. Participants included 403 adults (152 males and 252 females, mean age = 24.20) who provided genetic data and a set of the questionnaires (BIS11; Barratt Impulsiveness Scale-11 and EMBU; Egna Minnen av Bätraffande Uppfostran). Using SEM (Structural Equation Modeling), we evaluated 3 models for both direct and indirect relationships between 5-HTTLPR (5HTT) and Impulsivity (IMP), via maternal/fraternal rejection (MAT/FAT). In model 1, the direct path from 5HTT and IMP was not significant across the mother’s and father’s analysis. Models 2 and 3 assessed the indirect influence of 5HTT on IMP through MOT/FAT. The paths of models 2 and 3 were all significant and showed a good fit between the hypothesized model and data. Furthermore, the effects of the 5-HTTLPR genotype on impulsiveness in this Japanese sample were particularly accounted for by perceived rejection from the mother or father. The effects from the parents appeared to be robust especially among males. These results may help elucidate the specific pathways of risk in relation to genetic and environment influences on impulsive phenotypes.